Motivational Impacts of the Google Docs Integration to Support Collaborative Writing: A Review Approach - Sharifahtun Naim, Shahidan; Zuraina, Ali; Norsuhaily, Abu Bakar (SRN Intellectual Resources, 2022)
In recent decades, various digital technology tools such as Google Docs, wikis, and other collaborative writing platforms have shifted the writing perspectives from product-based to process-based writing. Motivation is a crucial component in developing learners' writing skills. It is not feasible to study if one lacks motivation. Therefore, the function of motivation in student learning is crucial to ensure effective writing among students. This paper presents a review of the current trends in the integration of Google Docs in collaborative writing. The review includes critical and analytical discussions on the motivational impact of using Google Docs to support collaborative writing. This study employed content analysis as a data analysis method. The findings show that Google Docs is beneficial to creating a supportive and motivating learning environment for learners. This paper suggests that more studies should be conducted to comprehensively explore the integration of Google Docs in collaborative writing in terms of learning outcomes and attitudes, particularly in the Malaysian higher education setting. Furthermore, examining studies on teachers' attitudes toward collaborative writing and Google Docs integration is highly advised.